A extrafiscalidade tributária e a proteção ambiental no Mercosul - Coronel, Loraine Terezinha Bicca Carmo (2008)
The state has several tools for environmental preservation, among them, extrafiscal Topping the tribute. The aim of this research is to determine whether the extrafiscalidade tax is a skillful instrument for the implementation of a policy of environmental preservation in Mercosur. For both from the law and doctrine, he worked with the deductive method, a descriptive and analytical research literature and public documents, among books, periodicals, domestic and foreign. We analyzed the protection of the environment in Mercosur, the way reporting is being done to protect the environment in the countries of the bloc, namely its environmental policies, based on the analysis of the Environmental Law, from the recognition in the constitutional level, in their four Member States. We dealt with state intervention by the enunciation of the purposes that the State seeks to achieve through its financial activities, to conceptualize extrafiscalidade and described itself as the ways to materialize, were also highlighted some of the purposes extrafiscais present in the Brazilian tax system. We examined the principles of law and the Environmental taxation principles relevant to the Environmental taxation, it was determined the tax jurisdiction in environmental matters in Brazil and, finally, the species have been tabled tax consistent with the Environmental taxation from the conceptual analysis of taxes National Tax System established in Brazil. Finally, this was the Environmental taxation issue, with clear extrafiscalidade aiming modify pipelines with a view to sustainable development, given the Magna Carta of many countries as ideal for growth and social welfare. It was found that in countries where taxes are used, in order extrafiscal, there is an increase in quality of life. The implementation of fiscal policies, which use the mechanisms of environmental extrafiscalidade tax, as well as reach the final destination of control, preservation and restoration of the environment can give the taxpayer the opportunity to choose between the more mild peeve, or even the unburden themselves of the tax peeve, according to their performance according to legal dictates. It has been proved that Mercosur has a policy of protecting the environment as a result of the activities of TMS-6, power to dictate the basic guidelines for environmental policy in MERCOSUR. However, States Parties are still acting on the environmental issue separately, indicating that environmental policy for MERCOSUR is more rhetoric than practice. It was concluded that a policy of environmental preservation can be effected through the creation of taxes, fees, contributions for improvement, contributions to intervene in the economic domain and the granting of fiscal incentives, consisting in the past two ways most suitable for this purpose. It was proven that the tax is extrafiscalidade skillful instrument for the implementation of a policy of environmental preservation in Mercosur, as it personifies the end state of environmental intervention.